PERAN PEMERINTAH DESA DALAM MITIGASI BENCANA DI DESA BONTO KATUTE KECAMATAN SINJAI BORONG KABUPATEN SINJAI - Usbar, Usbar; Syamsuddin, Syamsuddin; Wahid, Abd (Universitas Muhammadiyah Lampung, 2025)
This study aims to analyze the role of village governments in disaster mitigation efforts in Bonto Katute Village, Sinjai Borong District, Sinjai Regency. This village is an area with hilly geographical conditions that are prone to landslides and strong winds, so it demands an effective mitigation strategy. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews with village and community officials, and documentation. Based on preliminary data, the number of people affected by the landslide disaster until 2024 is 21 households. With limited infrastructure, human resources, and funding are common obstacles in the implementation of optimal mitigation in this village. The results of the study show that the Bonto Katute Village government has played a fairly active role in disaster mitigation through several main aspects. First, the integration of mitigation programs into village development planning and the preparation of village regulations that support environmental conservation. Second, the implementation of socialization and community education routinely collaborates with the Sinjai Regency BPBD. Third, the development of mitigation infrastructure such as soil retaining talud, drainage, and evacuation routes financed through village funds. Fourth, the provision of emergency facilities and the formation of disaster preparedness community groups as an effort to strengthen citizens' preparedness. Fifth, cross-sector coordination with BPBD, TNI, Polri, and NGOs in disaster management, both during emergency response and post-disaster rehabilitation. However, this study also found a number of obstacles such as budget limitations, low awareness of some people in protecting the environment, and lack of early warning technology. Overall, the role of the village government in disaster mitigation in Bonto Katute Village is quite good even though it is not optimal. Therefore, it is necessary to optimize the budget, increase public awareness, use simple technology for early warning, and strengthen the institution of disaster preparedness villages so that Bonto Katute Village can become a disaster-resilient village in Sinjai Regency.